"I Like My Peeps": Diversifying the Net Generation's Digital Leisure. (4th July 2017) - Valtchanov, Bronwen L.; Parry, Diana C.
ABSTRACT: The current generation of adolescents is the first to have grown up with the widespread use of the internet as part of their everyday lives; they are the Net Generation. To diversify existing research on this generation's digital practices, this study explored the intersectional experiences of diverse immigrant adolescent girls' digital leisure. Conversational interviews with nine girls revealed that they encountered numerous interpersonal leisure constraints following their immigration to Canada. Within their digital leisure, girls were able to negotiate these constraints through online connections with family and friends back home, Canadian friends, and the global village. These online connections facilitated an expansion of social boundaries and communication with both familiar and broad networks to maintain and develop relationships, pursue interests, share culture, and resist limiting gendered norms with the unparalleled interactivity and sociability of digital leisure.